How individual differences in sensory coding and attentional control impact understanding speech in noise - Shinn-Cunningham, Barbara; Ruggles, Dorea; Choi, Inyong; Bharadwaj, Hari; Mehraei, Golbarg; Dai, Lengshi (The Journal of the Acoustical Society of America, 2016)
Historically, the majority of psychoacoustic studies of hearing ability have viewed individual differences as noise: a nuisance that makes it difficult to see the effects that different acoustic conditions have on auditory perception. This talk reviews how we have begun to use individual differences to tease apart the processes that affect perception, with a particular focus on how listeners understand speech when there are competing sound sources. We find that individual subjects show consistent differences in their ability to understand speech in noise. These consistent differences can come both from differences in the fidelity of sensory coding and from differences in the ability to focus selectively on important sound and suppress unimportant sound. Importantly, which of these factors predicts performance depends greatly on the details of the stimuli used in a given task, and what stage of processing is the resulting bottleneck, determining performance. When fine differences in the sound content, such as small differences in location or pitch, are critical for a task, differences in sensory fidelity dominate individual differences in ability. However, when the acoustic features important for separating sound streams and identifying the target stream from the mixture are very distinct, individual differences in ability reflect differences in attentional control. These results highlight how understanding speech in noise depends on complex interactions between the ear and the brain.